Sex ratio in offspring of those affected by dioxin and dioxin-like compounds: the Yusho, Seveso, and Yucheng incidents. Issue 8 (1st August 2001) - Yoshimura, T; Kaneko, S; Hayabuchi, H
Abstract : Sex ratios in the offspring of those affected by dioxins or dioxin-like compounds have been reported from Seveso, Italy and Yucheng, Taiwan. The sex ratio of live births in Yusho, Japan after a similar accidental massive exposure to polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs) in 1968 are reviewed. Data on all births among parents exposed to the compounds from 1968 to 1977 in Fukuoka and a region of Nagasaki, the two areas affected, are reported. In total there were 85 live births in those regions. The sex ratio was not significantly different from normal (0.513). To evaluate hormonal disrupting activity or effects on reproductive outcome by PCBs and PCDFs, a further investigation of sex in offspring of the Yusho victims, especially offspring of those who were younger than 19 years of age at the time of the Yusho incident, is needed.